The Communication of Viewpoints in Jordanian Arabic: A Pragmatic Study - Al-khawaldeh Nisreen; Abu Rahmeh Luay (Open Linguistics, 2022)
Expressing opinions is considered a significant communicative act frequently taking place in our conversations. It is one of the fairly neglected areas of research in the Arabic context. Among the studies conducted on the communicative acts, to the best of our knowledge, there has been no attempt to investigate the expressions of opinion and its strategies specifically in Jordanian Arabic (JA). To this end, the current study intends to investigate the communicative act of opinion giving in JA with reference to gender disparities. Data elicited from 50 male and 50 female speakers of JA via Discourse Completion Task and role-plays revealed that Jordanians resort to a mixture of expressions to convey their opinion clearly. They use various types of strategies, including direct expression of opinion, indirect manifestation of opinion, advice, suggesting, enumeration, prayers, address terms, complaining, personalized hedges, and rarely opting out. In addition, gender differences were also noticed in expressing this speech act. Males use direct expression strategy and imperative expression significantly more than the female participants, whereas the females used six strategies significantly more than their male counterparts: indirect expression, advice, personalized hedges, suggesting, prayers, and address terms.